Interventional Treatment for Cholangiocarcinoma - Li, Hang; Chen, Li; Zhu, Guang-Yu; Yao, Xijuan; Dong, Rui; Guo, Jin-He (Frontiers in Oncology, 2021)
Cholangiocarcinoma (CCA) is the second most common type of primary liver malignancy. The latest classification includes intrahepatic cholangiocarcinoma and extrahepatic cholangiocarcinoma, with the latter one further categorized into perihilar and distal cholangiocarcinoma. Although surgical resection is the preferred treatment for CCA, less than half of the patients are actually eligible for radical surgical resection. Interventional treatment, such as intra-arterial therapies, ablation, and brachytherapy (iodine-125 seed implantation), has become an acceptable palliative treatment for patients with unresectable CCA. For these patients, interventional treatment is helpful for locoregional control, symptom relief, and improving quality of life. Herein, in a timely and topical manner, we will review these advances and highlight future directions of research in this article.